MANAJEMEN STRATEGI RUMAH ANAK PRESTASI NGINDEN DALAM MENDUKUNG PENYANDANG DISABILITAS DI KOTA SURABAYA TAHUN 2023 - Shabirah Putri Azzahra; Vidya Imanuari Pertiwi (LPPM Universitas Abdurrab, 2024)
Surabaya is the second largest city in Indonesia with the largest population, this does not make the Surabaya City Government silent, but continues to make breakthroughs, including in fulfilling the rights of children with disabilities so that Surabaya City has managed to excel from other cities by being named a Primary Level Child Friendly City for five consecutive years. The Surabaya City Government inaugurated a house or place of learning for children with disabilities in Surabaya City called